The Spill Over Effect of Bitcoin on Fiat Currencies: A Study on Pre and Covid Period - Nur, Triasesiarta; Ariefianto, Moch. Doddy; Kevin, Kevin; Sharon, Daniel (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2024)
We investigate the spillover effect from Bitcoin to selected Fiat currencies (Major and Emerging currencies) using the USD index as control. Our dataset comprises daily frequency from 2 composite currency indices, 7 Major currencies and 21 Emerging Market (EM) currencies from 01/01/2014 to 29/10/2021 (2042 observations). Applying the Dynamic Conditional Correlation - Generalized Autoregressive Conditional Heteroscedasticity (DCC-GARCH) method, we find evidence of spillover with changing patterns (from largely no spillover to negative spill over) between pre- Covid versus COVID-19 period. During the COVID period, Bitcoin demonstrates hedging capabilities against USD.